Acknowledging others as 'whole beings'.Managers' perceptions of spirituality and health in the South African workplace. (June 2014) - Honiball, George; Geldenhuys, Dirk; Mayer, Claude-Hélène
Abstract This article explores the concept of spirituality within selected South African managerial work contexts. The aim of the study was to determine managers' perceptions of spirituality and health-related aspects in various South African workplaces. A phenomenological research paradigm was used, applying an in-depth qualitative research approach. The sample consisted of 12 senior managers from different organizations, including, for example, an international healthcare provider, an international auditing and consulting firm, a manufacturer of paint supplies and decorations and an ecclesiastical organization. Research methods included semi-structured interviews and observation. Data was analysed through content analysis, identifying themes, categories and codes. The findings indicate that spirituality promotes the development of health-related aspects of individuals, such as self-awareness, inner peace and the management of stress and depression. Managers emphasize that spirituality also has an impact on managing teams and teamwork, engaging in competitive behaviour, encouraging honesty and reducing selfishness. Based on the findings, a conclusion is given and practical as well as scientific recommendations are emphasized. <disp-quote> In love lies the seed of our growth. The more we love, the closer we are to the spiritual experience. (Paulo Coelho, 1994) </disp-quote>